Application of virtual reality. Psychic-physical and sports neurorecovery agent - Manuel Ortega Caballero; Margarida Pedrosa de Lima; Antonia Ortega Caballero (INFAD, 2017)
There are not many studies on how to directly influence the emotions and education of people through virtual reality (VR3D) and its positive cardiovascular effects after exercise. The educational video is a didactic means that facilitates the discovery of knowledge and the assimilation of these, therefore we must also check the effectiveness of virtual reality, and specifically about our physical and psychic state. It is also motivating for the subject as the 3D image and HQ sound capture attention with great ease. The present study was carried out with 120 subjects of different ages. 120 personal interventions and assessments were established. To collect the information and its subsequent transcription, through the visualization of virtual reality films. Positive exercise since we discovered numerous parameters among them the effectiveness on the physiological stress. This psychic and methodological intervention (VR3D) in future professionals emphasizes the importance of training in new technologies and their benefit at cardiovascular and emotional level of subjects in their physical activity